Poesia e emancipação: análise de alguns poemas de A rosa do povo de Drummond em diálogo com Paulo Freire - Auzier, João Pedro Teles (2024)
Carlos Drummond de Andrade is an exponent of Brazilian modernist poetry. The Minas Gerais poet's works cover a wide range of themes. But they are especially incisive when it comes to freedom, especially in the book A Rosa do Povo (2000), which the poet published in 1945. In the light of Paulo Freire's educational theories, especially the book Pedagogia do Oprimido (1987), Drummod's poetics become even more powerful, because Paulo Freire believes in liberating, collective education, an experience in which everyone can develop through the generous dialogue that should characterize the teaching-learning experience. This master's dissertation combines Freire's reflections with an analysis of some poems from A Rosa do Povo, a book marked by the search for freedom, autonomy and emancipation, key words in Freire's vocabulary, which we will detail throughout the dissertation. In order to contribute to the poet's critical fortune, our reading conceives the interaction with the poetic word as a decisive factor for a relationship with language and with knowledge that deeply touches the process of the subject's awareness of historical experience, going beyond a passive reception of knowledge, the merely mechanical and instrumental spelling so criticized by the educator: "all men return home. / They are less free, but they carry newspapers / and they spell out the world, knowing that they have lost it," say lines from Drummond's “A Flor e a Náusea” (2000, p. 15). Thus, engaging in this historical experience through education, in Freire, as much as through poetry, in A Rosa do Povo, would involve building a critical and free attitude towards language and its practices of naming the world